Correlation between endogenous VWF:Ag and PK parameters and bleeding frequency in severe haemophilia A subjects during three‐times‐weekly prophylaxis with rFVIII‐FS. (20th November 2013) - Lalezari, S.; Martinowitz, U.; Windyga, J.; Enriquez, M. M.; Delesen, H.; Schwartz, L.; Scharrer, I.
Summary Patients with severe haemophilia A experience frequent and spontaneous bleeding, causing debilitating damage to joints and decreasing quality of life. Prophylaxis with factor VIII (FVIII) reduces joint damage if initiated early. Circulating FVIII levels may be influenced by endogenous von Willebrand factor (VWF), a chaperone protein that binds and stabilizes FVIII. The aim of this study was to determine whether endogenous VWF antigen (VWF:Ag) levels are correlated with FVIII pharmacokinetic (PK) parameters and clinical outcomes in patients with severe haemophilia A. Previously treated, non‐inhibitor patients in a multinational, randomized, double‐blind, Ph II study received prophylaxis with once‐weekly BAY 79‐4980 (35 IU kg−1) or thrice‐weekly recombinant sucrose‐formulated FVIII (rFVIII‐FS; 25 IU kg−1). PK parameters were evaluated at weeks 1 and 26. The number of bleeds per patient during the study was captured as part of the core efficacy endpoint. Spearman rank correlations assessed relationships of VWF:Ag levels with patient age, PK and annualized bleeding rate. Of 131 study patients (aged 13−64 years; BAY 79‐4980, n = 63; rFVIII‐FS, n = 68), 27 (21%; n = 15 and 12 respectively) were evaluable for PK assessment. Baseline VWF:Ag levels correlated with patient age (P < 0.0001). There was no significant difference in PK results between treatments; thus, PK parameters and VWF levels of all patients were analysed together. AUCnorm and T1/2 significantly increased with increased VWF:Ag (P < 0.001); clearance significantly decreased with increased VWF:Ag (P = 0.002). Annualized bleeding rate in patients treated with 3× per week rFVIII‐FS significantly correlated with VWF:Ag and age (P = 0.038 and 0.021 respectively). PK parameters as well as the clinical outcome significantly correlated with endogenous VWF:Ag. The improved clinical outcome in subjects with high VWF:Ag levels may be explained by VWF:Ag influence on FVIII PK.